Evaluación del efecto de Metarhizium en el control de larvas de Delia platura durante la etapa germinativa en el cultivo de Chocho (Lupinus Mutabilis Sweet), cantón Pujilí, barrio el Tingo Grande - Viera Albán, Kelly Gabriela (2023)
The present investigation was carried out in the "El Tingo Grande" neighborhood belonging to the La Matriz parish of the Pujilí canton, with the purpose of evaluating the effect of Metarhizium on the control of Delia Platura larvae in the lupine crop (Lupinus Mutabilis Sweet). , for the effect the quantitative methodology in laboratory and field was used; With two study variables (frequency of application and dosage), an experimental design of Completely Random Blocks (DBCA) was applied, of 4x3 with 3 repetitions giving a total of 36 experimental units.